Estudio y análisis del emisor de Bancolombia en la Bolsa de Valores de Colombia (2022)
With the purpose of predicting future trends and analyzing past and presentation trends to know the approximate behavior of the price, or simply a trend, for this we will use indicators such as EBITDA, which will allow us to provide strategies that will demonstrate the value, risk and profitability of investing in a Preferred Stock, showing us if it is a reliable company at the time of investing and being able to make a wise investment decision. Even in the current year it is crucial, since due to the pandemic the Stock Exchange and its issuers are really hit and how they went through this situation, due to the pandemic the world stock exchanges collapsed and the world economy was terribly affected.